Efficacy and tolerability of switching therapy to vortioxetine versus other antidepressants in patients with major depressive disorder. (1st February 2016) - Brignone, Mélanie; Diamand, Françoise; Painchault, Caroline; Takyar, Shweta
Abstract: Objectives: To assess the relative efficacy and tolerability of vortioxetine against different antidepressant monotherapies in patients with major depressive disorder (MDD) with inadequate response to selective serotonin reuptake inhibitor (SSRI) or serotonin–norepinephrine reuptake inhibitor (SNRI) therapy. Methods: A systematic search was conducted for monotherapy studies in patients with MDD with inadequate response to first-line therapy. Treatments included SSRIs, SNRIs, and other antidepressants. Identified studies underwent a three-stage screening/data extraction process and critical appraisal. Adjusted indirect treatment comparisons (ITCs) on systematic literature review outputs were made using Bucher's method, comparing remission rates and withdrawal rates due to adverse events (AEs). Results: Of 27 studies meeting the inclusion criteria, a few studies were of high quality according to the National Institute of Health and Care Excellence checklist. Three studies contributed to an evidence network for quantitative assessment comparing vortioxetine with agomelatine, sertraline, venlafaxine XR, and bupropion SR. Vortioxetine had a statistically significantly higher remission rate than agomelatine (risk difference [RD]: −11.0% [95% CI: −19.4; −2.6]), and numerically higher remission rates than sertraline (RD: −14.4% [95% CI: −29.9; 1.1]), venlafaxine (RD: −7.20% [95% CI: −24.3; 9.9]), and bupropion (RD: −10.70% [95% CI: −27.8; 6.4]). Withdrawal rates due to AEs were statistically significantly lower for vortioxetine than sertraline (RD: 12.1% [95% CI: 3.1; 21.1]), venlafaxine XR (RD: 12.3% [95% CI: 0.8; 23.8]), and bupropion SR (RD: 18.3% [95% CI: 6.4; 30.1]). Conclusions: The current systematic literature review found a few high quality switch studies assessing monotherapies in patients with MDD with inadequate response to SSRI/SNRIs. ITCs indicated that switching to vortioxetine leads to numerically higher remission rates compared with other antidepressants. Vortioxetine is a well tolerated treatment, showing statistically lower withdrawal rates due to AEs compared with other antidepressants. Vortioxetine is a relevant therapeutic alternative in patients experiencing inadequate response to prior SSRI or SNRI therapy.